2022
DOI: 10.3389/fspas.2022.787567
|View full text |Cite
|
Sign up to set email alerts
|

Organic Molecules in Interstellar Space: Latest Advances

Abstract: Although first considered as too diluted for the formation of molecules in-situ and too harsh an environment for their survival, the interstellar medium has turned out to host a rich palette of molecular species: to date, 256 species, not counting isotopologues, have been identified. The last decade, and more particularly the last 2 years, have seen an explosion of new detections, including those of a number of complex organic species, which may be dubbed as prebiotic. Organic molecules have been discovered no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 102 publications
0
54
0
Order By: Relevance
“…Organic species are present in the interstellar medium; protoplanetary disks; interplanetary dust particles; and primitive bodies including asteroids, comets, and interplanetary dust particles (see [ 56 , 243 , 244 , 245 , 246 ] and references therein). Organic delivery from exogenous sources has been suggested in the past (see [ 247 , 248 , 249 ] and references therein) as potentially important in seeding planets with the ingredients for life.…”
Section: Brief Discussion Of Organicsmentioning
confidence: 99%
“…Organic species are present in the interstellar medium; protoplanetary disks; interplanetary dust particles; and primitive bodies including asteroids, comets, and interplanetary dust particles (see [ 56 , 243 , 244 , 245 , 246 ] and references therein). Organic delivery from exogenous sources has been suggested in the past (see [ 247 , 248 , 249 ] and references therein) as potentially important in seeding planets with the ingredients for life.…”
Section: Brief Discussion Of Organicsmentioning
confidence: 99%
“…The first molecule in the polyyne series, C 4 H 2 , has been recently detected in the C rich AGB star IRC +10216 (Fonfría et al, 2018), and the first two polyynes, C 4 H 2 , C 6 H 2, and benzene were found in the protoplanetary nebula CRL 618 (Cernicharo et al, 2001), but the next steps toward the formation of polyaromatic molecules are largely unknown. As mentioned above, the first detection of a polyaromatic molecule, the bicyclic molecule indene, has taken place recently (Burkhardt et al, 2021;Cernicharo et al, 2021) in the molecular cloud TMC-1, an environment with a chemistry quite different from that of AGB and post AGB stars (Guélin and Cernicharo, 2022). To investigate the evolution of acetylene in the reactions with C atoms and C 2 dimers present in the inner shells of AGB stars, Santoro et al (2020) used the "Stardust" set up (Martínez et al, 2020 and Figure 5), but introduced C 2 H 2 , instead of H 2 , in the sputtering chamber.…”
Section: Carbonaceous Dust Productionmentioning
confidence: 96%
“…Radical species in the ISM play a vital role in forming complex organic molecules (COMs). [25][26][27] To understand the chemical evolution in the ISM, it is essential to understand the elementary radical process, such as radical adsorption, diffusion and chemical reactions on the ice mantles of interstellar grains. Accumulation of the primary radicals on the icy grain surfaces may occur at very low temperatures (e.g., 10 K) in dark clouds.…”
Section: Applications Of Pyqm/mmmentioning
confidence: 99%